Development of professionalism vignettes for the continuum of learners within a medical and nursing community of practice - Smyth, Penelope; Birkman, Clair; Hodgson, Carol S (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2021)
Background: It is challenging to develop professionalism curricula for all members of a medical community of practice. We collected and developed professionalism vignettes for an interactive professionalism curriculum around our institutional professionalism norms following social constructivist learning theory principles.Methods: Medical students, residents, physicians, nurses and research team members provided real-life professionalism vignettes. We collected stories about professionalism framed within the categories of our Faculty’s code of conduct:  honesty; confidentiality; respect; responsibility; and excellence. Altruism was from the Nursing Code of Ethics. Two expert committees anonymously rated and then discussed vignettes on their educational value and degree of unprofessional behaviour. Through consensus, the research team finalized vignette selection.Results: Eighty cases were submitted: 22 from another study; 20 from learners and nurses; and 30 from physicians; and eight from research team members. Two expert committees reviewed 53 and 42 vignettes, respectively. The final 18 were selected based upon: educational value; diversity in professionalism ratings; and representation of the professionalism categories.Conclusion: Realistic and relevant professionalism vignettes can be systematically gathered from a community of practice and their representation of an institutional norm, educational value, and level of professional behaviour can be judged by experts with a high level of consensus.